Penanaman Sikap Moderasi Beragama Pada Siswa Sekolah Dasar Melalui Pembelajaran PAI - Silfia Dewi; M Afif Zamroni; Aris Adi Leksono (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This article aims to examine in depth the role of Islamic Religious Education Teachers in instilling an attitude of religious moderation in students at SDN 2 Kelod Kangin Semarapura Klungkung Bali and analyze its implementation and implications. A qualitative approach was used with data collection techniques through interviews, observation, and documentation of Islamic Religious Education Teachers, School Principals, learning processes, and interactions in the school environment. The results of the research show that Islamic Religious Education Teachers have a very important role, including providing exemplary examples with mutual respect and tolerance for religious differences, providing an understanding of religious moderation through interactive and participatory learning models in the classroom, and playing a role in creating good social interactions. Between students of different religions by upholding mutual respect, respect, and tolerance. The implementation of cultivating an attitude of religious moderation is carried out in three ways: the learning process in the classroom, interaction in the school environment, and interaction with the surrounding environment. In this implementation, it can be seen that Muslim and non-Muslim students respect each other and uphold tolerance by the values ??of religious moderation taught. The implication is that school policies are non-discriminatory in providing all students with the right to religious education and creating a sense of tolerance for students in broader social life. The research concludes that teachers strategically instil religious moderation through example, learning, and good social interaction. With proper implementation and supportive school policies, this effort positively impacts a more tolerant and harmonious social life.